ANALYZING NONVERBAL COMMUNICATION IN SEMINAR PRESENTATION - Ranta Butar-Butar (Universitas Musamus, Merauke, Papua, 2018)
Nonverbal communication is one of language elements in transfering messages to the others. Nonverbal communication can give contribution to make seminar presentation atmosphere more effective and interesting avoid from boredom feeling. The used of nonverbal communication can support the successfulness of a seminar presentation. In other different situations, it is can be used by teacher during classroom interaction to make students easier to understand the teaching and also to make the classroom interaction more active. The objectives of this research were to find out the verbal, kinds of nonverbal communication and the audience’s perception about the use of nonverbal communication in Seminar Presentation. The objects of this research were the students at graduate program State University of Makassar. The approach employed in this research was qualitative approach. Data collection of this research was conducted through observation by recording and interview. Data from observation was used to know the verbal and kinds of nonverbal communication. Interview was used to know the audience’s perception about using of nonverbal communication in seminar presentation. The research findings showed that (1) there were five kinds function of nonverbal communication in seminar presentation. Presenter used his hand gestures when he complemented his explanation or gave additional information to complement his verbal messages. Presenter used his head nod while repeating his verbal messages. To emphasize or reinforced his verbal communication, presenter used hand gestures, such as tap a pen to reinforce his explanation. Presenter used smile as facial expressions to substitute that she was agree with the examiner. Then, to regulate his verbal messages presenter used hand gestures and play eye contact to manage and control his verbal communication. (2) The findings revealed that the kinds of nonverbal communication used by the presenters were five types in seminar presentation. Presenter used head nod as indicated his agreeing with the examiner’s response. Hand gestures eye contact, facial expressions, and body movement those are the most frequently used by presenter in seminar presentation. (3) The last, the findings showed that audience’s perception stated that the using of nonverbal communicaton iin seminar presentation is important to be applied because it can be make seminar’s atmhosphere was more effevtive and interesting